A comprehensive experimental setup for identification of friction model parameters. (June 2016) - Sun, Yun-Hsiang; Chen, Tao; Wu, Christine Qiong; Shafai, Cyrus
Abstract: Parameter identification for advanced friction models is the most demanding task and involves a wide range of experimental dynamic analysis. The identification results directly affect the quality of the friction model and significantly depend on the setup. While many setups have been proposed to investigate the various characteristics of friction, rather less attention has been paid to designing one that is practical for parameter identification dedicated to certain common models. An experimental setup featuring simplicity, flexibility and good versatility is proposed here. The setup consists of a mass block connected to a motor-powered ball screw mechanism. Such a block slides on a metal base and the friction at the contact junction is varied accordingly. The materials and lubricants in the contact surface can be easily altered if needed. A capacitance displacement sensor is designed and installed at where the precise presliding profiles can be captured. The experimental setup, the calibration procedure for the displacement sensor and the experimental results are presented. It is shown that the experimental data produced by our setup leads to the success in parameter identification procedures of the selected friction models. Some limitations of the friction models, from the perspective of parameter identification, are discussed. Highlights: A practical experimental setup for parameter identifications of popular friction models is proposed, featuring simplicity, flexibility, and good versatility. The contact conditions at the frictional surfaces can be easily altered to examine the friction behaviors subject to wide range of contact conditions. With the proposed setup, features of friction in either presliding or gross-sliding regime can be accurately captured. It is an effective and valuable setup for friction-related studies.